Systemic antibiotic therapy of patients with acute bacterial sinusitis taking into account resistance - S. V. Starostina; D. A. Sivokhin (Медицинский совет, 2021)
Acute rhinosinusitis is one of the most common diseases in the world. According to statistics, about 10 million cases are registered in Russia every year.Acute bacterial rhinosinusitis (ABRS) in most cases develops as a result of an acute respiratory viral disease, proceeds easily and it does not require antibiotic therapy. However, it significantly reduces the patient's quality of life in cases of moderate and severe disease, and in the absence of timely treatment, can lead to intracranial complications (meningitis, encephalitis, intracranial abscesses, etc.) and orbital (reactive edema of the eyelid, phlegmon of the orbit, periorbital abscesses, etc.). To avoid complications, with exacerbation of rhinosinusitis, it is necessary to choose the right antibiotic therapy, taking into account the resistance of the microorganisms that caused the disease.The article describes the differential diagnosticprinciples of bacterial rhinosinusitis according to the latest recommendations and research in this area, the most common antibiotic-resistant pathogens in the practice of an ENT doctor are presented, the issue of choosing the correct systemic antibiotic therapy for the treatment of patients with moderate and severe acute bacterial rhinosinusitis is considered according to modern data on the sensitivity of bacterial pathogens to antibacterial drugs prescribed in the otorhinolaryngologist's practice. The article presents data on a new universal cephalosporin of the 3rd generation (the active ingredient is cefditoren), as a second- and third-line drug, due to its high activity against most causative agents of acute bacterial rhinosinusitis, and clinical observation using the above antibacterial agent within the framework of the considered topics.